Harmonic Distortion Caused by Multilevel Current Source Inverters - König, Simon; Herold, Gerhard (Renewable Energy & Power Quality Journal (RE&PQJ), 2014)
Due to power electronic reasons and the cheaper construction possibilities of the link capacitors, the voltage source based topology is nowadays the state of the art. With the multilevel possibility the next step in inverter technology was taken and again the professional discussion mainly focusses on the voltage source inverters. This paper shall explain the approach of using a multilevel current source inverter instea
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.leen.harmon
Keywords: Multilevel Current Source Inverter; Harmonics; Power Quality